The role of thiols in the activation of the platelet integrin αllbβ3 - O'Neill, Sarah (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2001)
Platelets play a vital role in maintaining normal haemostasis. They circulate passively in the blood in an non-adhesive slate as discrete smooth discs. When platelets encounter a vessel wall injury or are exposed to foreign surfaces they undergo a leries of processes resulting in platelet activation. This leads to the formation of a localised haemostatic plug, which is stabilised by fibrin and ultimately prevents further blood loss from the vessel. These events are mediated through the interaction of adhesive macromolecules, such as plasma fibrinogen, with specific receptors present on the platelet membrane, most notably the platelet integrin αIIbβ3, in response to extracellular signals. This integrin neceptor is the most abundant protein on the platelet surface. It is a cysteine-rich heterodimeric adhesion molecule that alters conformation in response to platelet activation and ligand binding. The mechanisms involved in these conformational changes are not fully elucidated. It is the purpose of this study to identify a physiological mechanism that permits αIIbβ3 to undergo conformational changes to make it competent to bind ligand upon platelet activation.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin